The Role of the Center-Based Learning Model in Early Childhood Literacy Development: A Systematic Literature Review - Munadaroh, Erah; Mustapa, Noviana; Amini, Mukti (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to examine the role of the center-based learning model in early childhood literacy development through a systematic literature review approach. Early literacy is a critical foundation for children’s cognitive, language, social, and character development, necessitating instructional models that align with their developmental characteristics. This study employed the PRISMA 2020 framework to systematically identify and analyze relevant literature. Data were collected from national and international journal articles published within the last ten years, selected based on inclusion criteria such as children aged 5–6 years, the application of center-based learning or Beyond Centers and Circle Time (BCCT), and a focus on literacy development. A total of ten articles were analyzed using descriptive and narrative techniques. The findings reveal that the center-based learning model significantly enhances early literacy skills, particularly in language development, symbolic thinking, communication, and meaning-making through structured, play-based activities. Additionally, this model promotes children’s independence, creativity, and active engagement in learning. However, its implementation faces challenges related to teacher competence, limited facilities, and insufficient parental and institutional support. This study concludes that the effectiveness of center-based learning in improving literacy outcomes depends on well-organized learning centers, the integration of interactive literacy materials, and strong pedagogical facilitation by educators.